Toxicological evaluation of different pesticides in Tetragonisca angustula Latreille (Hymenoptera, Apidae) - Ana Lúcia Paz Barateiro Stuchi; Daiani Rodrigues Moreira; Adriana Aparecida Sinópolis-Gigliolli; Douglas Galhardo; José Ricardo Penteado Falco; Vagner de Alencar Arnaut de Toledo; Maria Claudia Colla Ruvolo-Takasusuki (Acta Scientiarum. Animal Sciences, 2022)
The stingless bee Tetragonisca angustula is an important pollinator of different agricultural and native crops. This study evaluated changes in the relative activity of esterases and critical electrolyte concentration in brain cells after exposure to pesticides malathion and thiamethoxam. Lethal concentration 50% showed greater toxicity of thiamethoxam in relation to malathion. Esterases EST-3 and EST-4 (carboxylesterase) were partially inhibited after contamination by contact and ingestion of malathion and contamination by contact with thiamethoxam, suggesting participation of these esterases in the metabolization of these compounds. The lowest critical electrolyte concentration (CEC) was found after contamination by malathion ingestion (0.15 M), indicating changes in gene expression. The alterations observed in the intensity of EST-3 and EST-4 and the chromatin structure indicate that pesticides can act in gene expression and be used as biomarkers of contaminant residues. Furthermore, knowing the susceptibility of T. angustula bees to pesticides, it would be possible to use this species for biomonitoring environmental quality in preserved areas and agroecosystems.